Laju perubahan kadar air dan vitamin c snack mi kering dalam kemasan dengan penambahan pasta bit sebagai sumber vitamin c - Rosalina, Yessy; Sembiring, Lisa Monica; Saputri, Ratna Yuni (Universitas Muhammadiyah Mataram, 2024)
Noodle snacks are snacks made from fried noodles, which are fried with the addition of seasonings. To improve the nutritional balance of dry noodle snack foods, it is necessary to conduct research by adding beetroot paste as a natural coloring and source of vitamin C. The purpose of this study is to determine the value of consumer preference for noodle snacks with the addition of beetroots and the rate of decline in snack quality. Dried noodles in packaging with the addition of beetroot paste as a source of vitamin C. The study used two types of packaging material, namely PE plastic and aluminum. Average organoleptic test value of noodle snack with addition of beetroot paste to quality attribute: aroma = 4.40; color = 4.32; taste = 4.36; crunchy = 4.28. The rate of quality decline in aluminum packaging against the variable of moisture content and vitamin C followed the rate of zero-order kinetics, with the value of the rate of increase in moisture content = 0.152. Meanwhile, the rate of decrease in vitamin C was -0.102. The results showed that the addition of beetroot paste to the making of noodle snacks was acceptable to the panelists. The addition of beetroot paste also provides a better vitamin C content, which is 3.75 mg/100g. Beetroot snack packaging using aluminum provides a lower rate of reduction in water content and vitamin C content compared to the use of PE plastic packaging materials.